Polonistyczne lekcje wrażliwości - Janus-Sitarz, Anna (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2012)
An inspiration for considerations on the role of a P olish philologist in the period of humanistic bankruptcy is a book by Elżbieta Mikoś entitled Lekcje empatii. The article concentrates on the issue of teacher’s responsibility in developing reader’s axiological sensitivity in his/her contact with a work (W.C. Booth) and boost difficulty as a challenge freeing the reader from the patterns of reading the world (H.‑G. Gadamer, J. Derrida). The author pays attention to the necessity of teaching how to listen to attentively as a basis of a good communication (J. Edgoose), as well as methodological pluralism as a condition of teaching an attitude of openness to new senses and alternative solutions.